Adaptation motor learning of arm movements in patients with cerebellar disease. Issue 5 (May 1996) - Deuschl, G; Toro, C; Zeffiro, T; Massaquoi, S; Hallett, M
Abstract : OBJECTIVE–To design a test of motor learning using arm movements in normal subjects and patients with cerebellar disease. METHODS–Elbow angle was continuously displayed as a cursor (a dot) on a computer screen, and subjects made ballistic elbow flexion and extension movements to try to move the cursor between two targets on the screen. The relation between the arm movement and its visual feedback was changed, and the subjects reacted by adapting the amplitude of their movements in subsequent trials. RESULTS–The consecutive errors showed exponential learning curves during adaptation, which were quantified by their steepness. Ten patients with isolated cerebellar or olivopontocerebellar degeneration had less steep learning curves than normal subjects, indicating a failure of adaptation motor learning in cerebellar disease. The results show that this test may be useful for the analysis of motor learning.